2021
DOI: 10.1101/2021.03.15.435375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The PfAP2-HS transcription factor protects malaria parasites from febrile temperatures

Abstract: Periodic fever is the most characteristic clinical feature of human malaria1-3, but how parasites survive febrile episodes is not known. While Plasmodium spp. genomes encode a full complement of chaperones4, they lack an ortholog of the conserved transcription factor HSF1, which in most eukaryotes activates the expression of key chaperones upon heat shock (HS)5-8. Here we identified PfAP2-HS, a transcription factor of the ApiAP2 family9-11, as the key regulator of the P. falciparum protective HS response. The … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…To assess whether DNA binding competition was specific to the AP2-EXP AP2 domain, we repeated competitive EMSAs with three different purified P. falciparum AP2 domains: AP2-I Domain 3 (AP2-I D3) 25,32 (Fig S3B) , AP2-HS Domain 1 (AP2-HS D1) 25,36 (Fig S3C) , and PfSIP2 Domain 1 (PfSIP2 D1) 35 (Fig S3D) , again using the minimum amount of protein needed to visualize binding of each ApiAP2 protein’s cognate DNA oligonucleotide (Table S2) . AP2-I D3 32 and PfSIP2 D1 35 are essential for the IDC, while ap2-hs deletion is tolerated when parasites are grown below physiological temperatures 36 . We found that Compounds A, B, C, and I can compete DNA binding by AP2-I (Fig S4A) , Compounds B and I compete DNA binding by AP2- HS D1 (Fig S4B) and Compounds B, C and I compete DNA binding by PfSIP2 D1 (Fig S4C) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess whether DNA binding competition was specific to the AP2-EXP AP2 domain, we repeated competitive EMSAs with three different purified P. falciparum AP2 domains: AP2-I Domain 3 (AP2-I D3) 25,32 (Fig S3B) , AP2-HS Domain 1 (AP2-HS D1) 25,36 (Fig S3C) , and PfSIP2 Domain 1 (PfSIP2 D1) 35 (Fig S3D) , again using the minimum amount of protein needed to visualize binding of each ApiAP2 protein’s cognate DNA oligonucleotide (Table S2) . AP2-I D3 32 and PfSIP2 D1 35 are essential for the IDC, while ap2-hs deletion is tolerated when parasites are grown below physiological temperatures 36 . We found that Compounds A, B, C, and I can compete DNA binding by AP2-I (Fig S4A) , Compounds B and I compete DNA binding by AP2- HS D1 (Fig S4B) and Compounds B, C and I compete DNA binding by PfSIP2 D1 (Fig S4C) .…”
Section: Resultsmentioning
confidence: 99%
“…These docking simulations resulted in a final list of S2). AP2-I D3 32 and PfSIP2 D1 35 are essential for the IDC, while ap2-hs deletion is tolerated when parasites are grown below physiological temperatures 36 S3. )…”
Section: In Silico Computational Modeling Of Ap2-exp Competitorsmentioning
confidence: 99%
See 1 more Smart Citation